Prevalence of Anxiety and Depressive Disorders in a Sample of Moscow Residents: Comparison of the GAD-7 and HADS Results with a Clinical Assessment - Valeriya I. Savenkova; Yana A. Zorkina; Alexandra G. Ochneva; Angelina I. Zeltzer; Darya A. Ryabinina; Anna M. Tsurina; Elizaveta A. Golubeva; Anna S. Goncharova; Irina V. Alekseenko; George P. Kostyuk; Anna Yu. Morozova (Consortium Psychiatricum)
BACKGROUND: Anxiety and depressive disorders are the most common mental disorders. Detecting a disorder at an early stage can prevent the development of severe disorders and preserve the patient’s functioning ability. Simple and reliable screening tools based on self-completion of questionnaires can be used for this purpose. However, it is not always the case that the scores of the self-questionnaire align with those of the clinician.